A castable material for resisting slag corrosion and a preparation method thereof

Through the combination and synergy of modified aluminum chromium zirconium corundum aggregate and other materials, the flexural strength, compressive strength and thermal shock stability of the castable are improved, and the problem of insufficient durability of traditional refractory castables is solved, and the problem of insufficient durability of traditional refractory castables is achieved. Effective protection and environmental protection performance of liquid aluminum.

CN118993707BActive Publication Date: 2025-01-07SHANDONG LUMING NEW MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411480167.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-07
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Traditional refractory castables are not durable in a long-term high-temperature complex chemical environment during aluminum smelting, resulting in damage to the melt pool, affecting production efficiency and safety, and are difficult to effectively resist slag corrosion.

Method used

Modified aluminum chromium zirconium corundum aggregate, modified corundum hollow spheres, alumina fine powder, electromelted aluminum magnesium spinel fine powder, modified chopped zirconium refractory fiber, coke gem fine powder, cyanite powder, oxidized The combination of aluminum powder, spodumene powder, bonding agent, water reducing agent and composite anti-permeability improvement agent can improve the flexural strength, compressive strength, thermal insulation performance, and thermal shock stability of the castable through modification treatment and synergistic action. and slag corrosion resistance.

Benefits of technology

The castable material has achieved high flexural strength, high pressure resistance, excellent thermal insulation performance, thermal shock stability and slag corrosion resistance, extends the storage cycle, and avoids pollution to aluminum liquid, reducing production costs and Environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of refractory materials, and in particular to a castable for resisting slag erosion and a preparation method thereof. A castable for resisting slag erosion, by mass, includes the following raw materials: 35-40 parts of modified aluminum-chromium-zirconium corundum aggregate, 10-12 parts of modified corundum hollow spheres, 8-10 parts of alumina fine powder, 10-12 parts of fused aluminum-magnesium spinel fine powder, 3-5 parts of modified short-cut zirconium-containing refractory fiber, 8-10 parts of coke gemstone fine powder, 3-5 parts of kyanite powder, 5-6 parts of alumina micropowder, 2-3 parts of spodumene powder, 3-4 parts of binder, 0.2-0.3 parts of water reducer, and 3-4 parts of composite anti-penetration improver. The castable for resisting slag erosion of the present application has high flexural strength and high compressive strength, and also has excellent thermal insulation performance, thermal shock resistance, slag erosion resistance and anti-penetration performance, and the castable has a long storage period and does not pollute the aluminum liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of refractory materials, and in particular to a castable material for resisting slag corrosion and a preparation method thereof. Background Art

[0002] Refractory castables are the most widely produced and used amorphous refractory materials, mainly used to construct various heating furnace linings and other integral structures. It is a granular and powdery material made of refractory substances, and a certain amount of binder and water are added to form it. It has high fluidity, is suitable for construction by pouring methods, and is an amorphous refractory material that can be hardened without heating. It is composed of refractory aggregates, powders, binders, admixtures, water or other liquid materials. It is generally cast and formed by pouring, vibrating or tamping at the site of use, and can also be made into prefabricated parts for use.

[0003] During the aluminum smelting process, the inner wall of the molten pool will be corroded by metal ions and non-metal ions, and will face the challenges of oxidation and reduction. Although traditional refractory castables can provide a certain degree of protection, their durability is often insufficient under long-term high temperature and complex chemical environment, resulting in damage to the molten pool, affecting production efficiency and safety. Therefore, the development of a castable that can effectively resist slag erosion and has both anti-oxidation and reduction properties has become an urgent need in the current field of refractory technology. Summary of the invention

[0004] The purpose of the present application is to provide a castable for resisting slag erosion and a preparation method thereof in view of the deficiencies in the current technology. The preparation method of the castable for resisting slag erosion of the present application has the advantages of simple preparation, low cost, energy saving and environmental protection. The obtained castable for resisting slag erosion has high flexural strength and high compressive strength, and also has excellent thermal insulation performance, thermal shock stability, slag erosion resistance and penetration resistance, long castable storage period, and does not cause pollution to aluminum liquid.

[0005] In a first aspect, the present application provides a castable for resisting slag corrosion, which adopts the following technical solution:

[0006] A castable for resisting slag corrosion comprises the following raw materials by weight: 35-40 parts of modified aluminum-chromium-zirconium corundum aggregate, 10-12 parts of modified corundum hollow spheres, 8-10 parts of alumina fine powder, 10-12 parts of fused aluminum-magnesium spinel fine powder, 3-5 parts of modified short-cut zirconium-containing refractory fibers, 8-10 parts of pyroxene fine powder, 3-5 parts of kyanite powder, 5-6 parts of alumina micropowder, 2-3 parts of spodumene powder, 3-4 parts of a binder, 0.2-0.3 parts of a water reducer, and 3-4 parts of a composite anti-penetration improver.

[0007] By adopting the above technical scheme, modified aluminum-chromium-zirconium corundum aggregate: as the main component of the castable, it provides good corrosion resistance and permeability resistance. Its structure is dense, hard, strong, and has good high-temperature stability, and can resist the erosion of alkaline aluminum liquid. Modified corundum hollow sphere: increases the thermal insulation and thermal shock stability of the castable. Alumina fine powder: improves the thermal insulation, thermal shock stability and corrosion resistance of the castable. Fused aluminum-magnesium spinel fine powder: has high melting point, small thermal expansion coefficient, good thermal shock resistance and strong corrosion resistance. Modified short-cut zirconium-containing refractory fiber: through modification, its dispersibility in the castable is improved, and the strengthening and toughening effect generated by its drawing action in the matrix is ​​used to improve the strength of the castable. Pyrope fine powder: through its excellent thermal shock stability and high-temperature performance, the comprehensive use performance of the castable is improved. Kyanite powder: as an expansion agent, the volume expansion generated by its irreversible decomposition at high temperature offsets the volume contraction of the castable at high temperature, thereby preventing cracking. Alumina powder, spodumene powder: through the sintering promotion effect, improve the sintering condition of the castable under the use conditions, promote the formation of high-temperature ceramic bonding phase, and improve the castable's ability to resist damage. Binder, water reducer: optimize the construction fluidity of the castable, reduce the amount of water added to the castable, and achieve the effect of high water reduction rate and no segregation. Composite anti-penetration improver: made by mixing carbon resin powder Carbores P and asphalt, it can enhance the bonding between particles, improve the liquid phase distribution at high temperature, avoid over-sintering, and significantly improve the castable's slag resistance. At the same time, carbon resin powder Carbores P can improve the castable's thermal shock resistance, high-temperature creep, corrosion resistance and anti-penetration properties.

[0008] Preferably, the preparation method of the modified aluminum-chromium-zirconium corundum aggregate comprises the following steps:

[0009] S11. According to the mass proportions, 100 parts of fine particles of fused zirconium corundum waste bricks with a particle size of 0.1-0.2 mm and 500 parts of fine particles of aluminum chromium waste bricks with a particle size of 0.1-0.2 mm are mixed evenly to obtain a mixture A, and then the mixture A is poured into a rolling ball mill, and a passivating agent is sprayed into the ball mill. The working parameters of the ball mill are adjusted to: a speed of 100 r / min, a power of 1500 kW, and a ball milling time of 2-3 hours to obtain a mixture B; wherein the spraying frequency of the passivating agent is 1 time / min, and the spraying dosage is 5 mL / cm 2 ;

[0010] S12. According to the mass proportion, 600 parts of mixed material B are used as raw materials to form a plate-shaped material layer with a thickness of 130 mm in a seat-cooled electric arc furnace. After arcing, 80-100 parts of coke material are sprinkled on the surface of the plate-shaped material layer at a frequency of 10 parts / min within 10 minutes, and the temperature in the furnace is adjusted to control 1600°C. After reacting for 8-10 hours, modified aluminum-chromium-zirconium corundum aggregate is prepared.

[0011] By adopting the above technical scheme, the role and synergistic effect of modified aluminum-chromium-zirconium corundum aggregate in castables are mainly reflected in the following aspects: 1. Slag erosion resistance: Modified aluminum-chromium-zirconium corundum aggregate has high slag erosion resistance and can effectively resist the erosion of acidic and alkaline aluminum liquid. This is because its structure is dense, hard, strong, and has good high-temperature stability. At the same time, due to its large wetting angle, it has strong resistance to aluminum liquid erosion and permeability. 2. Anti-penetration performance: The modified aluminum-chromium-zirconium corundum aggregate is firstly ball-milled with the fine particles of fused zirconium corundum waste bricks and aluminum-chromium waste bricks, and then arc-melted, making full use of the impurity components of the fine particles of fused zirconium corundum waste bricks and aluminum-chromium waste bricks to assist in melting. Spraying the passivator into the ball mill can form a dense oxide film on the surface of the aluminum-chromium-zirconium corundum aggregate in a short time, thereby improving the corrosion resistance and anti-penetration performance of the aluminum-chromium-zirconium corundum aggregate. 3. Thermal shock stability: The modified aluminum-chromium-zirconium corundum aggregate has high thermal shock stability and can effectively resist the influence of temperature changes on the material. This is because it has good thermal conductivity and low thermal expansion coefficient. 4. Improve the strength of the castable: The modified aluminum-chromium-zirconium corundum aggregate can improve the flexural strength and compressive strength of the castable through the synergistic effect with other raw materials. This is because it has high hardness and strength, which can enhance the overall strength of the castable. 5. Environmental performance: The modified aluminum-chromium-zirconium corundum aggregate is made of fused zirconium corundum waste brick fine particles + aluminum-chromium waste brick fine particles. It makes full use of waste resources, reduces production costs, and also reduces environmental pollution. In summary, the modified aluminum-chromium-zirconium corundum aggregate has many functions and synergistic effects in the castable, such as anti-slag erosion, anti-penetration, thermal shock stability, improving the strength of the castable and environmental performance.

[0012] Preferably, the preparation method of the passivator is: according to the mass parts, 55 parts of sodium metasilicate, 15 parts of straw charcoal, 8 parts of dodecyltrimethylammonium chloride and 22 parts of deionized water are stirred and mixed uniformly to obtain the passivator.

[0013] By adopting the above technical scheme, the preparation method of the passivator of the present application is simple, low in cost, environmentally friendly and harmless to the human body. Sodium metasilicate, as the main component, has good corrosion resistance and anti-penetration performance, and can effectively improve the surface corrosion resistance and anti-penetration performance of aluminum-chromium-zirconium corundum aggregate. Straw charcoal can effectively adsorb heavy metals in materials and reduce environmental pollution. Dodecyl trimethyl ammonium chloride, as a surfactant, can improve the fluidity of the passivator and improve the passivation effect on the surface of aluminum-chromium-zirconium corundum aggregate. Deionized water, as a solvent, can fully mix the various components to form a uniform passivator. The main function of the passivator is to surface treat the aluminum-chromium-zirconium corundum aggregate so that a thin oxide film is formed on its surface, thereby improving its corrosion resistance and anti-penetration performance. At the same time, the straw charcoal and dodecyl trimethyl ammonium chloride in the passivator can also effectively adsorb heavy metals in the material, reduce environmental pollution, and avoid harm to the human body. The synergistic effect of the passivator is mainly reflected in the following aspects: First, the synergistic effect of sodium metasilicate and straw charcoal can not only improve the corrosion resistance and penetration resistance of aluminum-chromium-zirconium corundum aggregate, but also absorb heavy metals in the material and reduce environmental pollution; second, the synergistic effect of sodium metasilicate and dodecyltrimethylammonium chloride can not only improve the fluidity of the passivator and improve the passivation effect on the surface of aluminum-chromium-zirconium corundum aggregate, but also further improve the corrosion resistance and penetration resistance of aluminum-chromium-zirconium corundum aggregate; third, the synergistic effect of sodium metasilicate, straw charcoal and dodecyltrimethylammonium chloride can not only improve the corrosion resistance and penetration resistance of aluminum-chromium-zirconium corundum aggregate, but also absorb heavy metals in the material and reduce environmental pollution, and at the same time improve the passivation effect on the surface of aluminum-chromium-zirconium corundum aggregate.

[0014] Preferably, the preparation method of the modified hollow corundum spheres is as follows: according to the mass fraction, 100 parts of hollow corundum spheres with a particle size of 1 mm are immersed in 200 parts of aluminum titanate solution with a mass concentration of 40% for 24 hours, the hollow corundum spheres after immersion are filtered, and dried at 850°C to obtain modified hollow corundum spheres.

[0015] By adopting the above technical scheme, the role of the modified corundum hollow sphere is to improve the thermal insulation performance and thermal shock resistance of the castable. Since the corundum hollow sphere has a low thermal conductivity and high strength, adding it to the castable can effectively reduce heat transfer, thereby improving the thermal insulation performance of the castable. At the same time, the addition of the corundum hollow sphere can also increase the internal porosity of the castable, so that it has better thermal shock resistance. In terms of synergy, the modified corundum hollow sphere and other raw materials such as modified aluminum chromium zirconium corundum aggregate, alumina fine powder, etc. can work together to improve the overall performance of the castable. For example, the modified aluminum chromium zirconium corundum aggregate can improve the flexural strength and compressive strength of the castable, while the alumina fine powder can improve the thermal insulation, thermal shock stability and erosion resistance of the castable. The interaction between these raw materials enables the castable to have the advantages of good thermal insulation, thermal shock stability, slag erosion resistance and anti-penetration performance while maintaining high mechanical properties.

[0016] Preferably, the modification method of the modified short chopped zirconium-containing refractory fiber comprises the following steps:

[0017] S41, according to the mass fraction, adding 10 parts of nano-montmorillonite to 20 parts of 25% hydrochloric acid solution, treating at 120° C. for 1.5 h, collecting the precipitate by filtration, washing and drying to obtain modified montmorillonite;

[0018] S42. Add modified montmorillonite, short-cut zirconium-containing refractory fibers with a length of 5-10 mm, magnesium chloride and aluminum chloride to a 6% sodium hydroxide aqueous solution according to their mass fractions. After ultrasonic dispersion for 1 hour, heat to 125°C under a nitrogen atmosphere for reaction for 20-24 hours. After drying, obtain modified short-cut zirconium-containing refractory fibers.

[0019] By adopting the above technical scheme, modified montmorillonite is obtained by adding nano-montmorillonite into a hydrochloric acid solution for treatment. The modified montmorillonite contains hydroxide, which can form hydrogen bonds with water, thereby improving the wettability of the material with water. This makes it easier for the castable to mix with water during the construction process, thereby improving the construction efficiency. In the process of preparing the modified short-cut zirconium-containing refractory fiber, the modified montmorillonite, the short-cut zirconium-containing refractory fiber, magnesium chloride and aluminum chloride are added to an aqueous sodium hydroxide solution for ultrasonic dispersion. Ultrasonic dispersion can make the components more evenly distributed in the solution, thereby improving the dispersibility of the short-cut zirconium-containing refractory fiber in the castable. This helps to improve the overall performance of the castable. The strength of the castable can be further improved by the strengthening and toughening effects produced by the drawing action of the modified short-cut zirconium-containing refractory fiber in the matrix. This is of great significance for improving the flexural strength and compressive strength of the castable during use. The short-cut zirconium-containing refractory fiber itself has good high temperature resistance. After modification, its dispersibility and wettability in the castable are improved, so as to better exert its high temperature resistance. This is of great significance for improving the service life and stability of the castable in a high temperature environment. The modified short-cut zirconium-containing refractory fiber and other raw materials (such as modified aluminum-chromium-zirconium corundum aggregate, alumina fine powder, etc.) work together to make the castable have excellent slag erosion resistance, thermal insulation performance, thermal shock stability and anti-penetration performance. At the same time, the castable has a long storage period and does not pollute the aluminum liquid, which meets the needs of practical applications.

[0020] Preferably, the mass ratio of the modified montmorillonite, the chopped zirconium-containing refractory fibers with a length of 5-10 mm, the magnesium chloride, the aluminum chloride and the sodium hydroxide aqueous solution with a mass concentration of 6% is 1:4:11:12:150.

[0021] Preferably, the average particle size of the pyroxene fine powder is 0.5 mm, the average particle size of the kyanite powder is 180 mesh, the average particle size of the alumina micropowder is 5 μm, the average particle size of the spodumene powder is 180 mesh, the average particle size of the alumina fine powder is 325 mesh, the average particle size of the fused aluminum magnesium spinel fine powder is 325 mesh, and the mass content of magnesium oxide in the fused aluminum magnesium spinel fine powder is 80%.

[0022] Preferably, the binder is calcium aluminate cement, and the weight percentage of aluminum oxide in the calcium aluminate cement is 75%.

[0023] The water reducer is prepared by mixing an aliphatic high-efficiency water reducer and a polycarboxylic acid-based high-performance water reducer in a mass ratio of 4:5.

[0024] By adopting the above technical scheme, the combination of aliphatic high-efficiency water-reducing agent and polycarboxylic acid high-performance water-reducing agent can reduce the viscosity of the castable, making it easier to flow during the construction process, thereby improving the construction efficiency. Due to the effect of the water-reducing agent, the amount of water added can be reduced while maintaining the fluidity of the castable, thereby reducing the water-cement ratio of the castable, which is beneficial to improving the strength and durability of the castable. Through the synergistic effect of aliphatic high-efficiency water-reducing agent and polycarboxylic acid high-performance water-reducing agent, a high water reduction rate can be achieved while avoiding segregation, making the performance of the castable more stable. The synergistic effect between aliphatic high-efficiency water-reducing agent and polycarboxylic acid high-performance water-reducing agent is mainly reflected in the following aspects: 1. Complementary effect: aliphatic high-efficiency water-reducing agent has a strong dispersing effect, while polycarboxylic acid high-performance water-reducing agent has a strong complexing effect. After the two are combined, their respective advantages can be fully utilized to achieve better water reduction effect. 2. Stabilizing effect: aliphatic high-efficiency water-reducing agent and polycarboxylic acid high-performance water-reducing agent can form a stable complex under certain conditions, which helps to maintain the stability of the castable and prevent the occurrence of segregation. 3. Regulation: By adjusting the ratio of aliphatic high-efficiency water-reducing agent and polycarboxylic acid-based high-performance water-reducing agent, the performance of the water-reducing agent can be adjusted according to actual needs to meet the requirements of different construction conditions. In summary, the water-reducing agent in this application is prepared by mixing aliphatic high-efficiency water-reducing agent and polycarboxylic acid-based high-performance water-reducing agent in a mass ratio of 4:5. Through the synergistic effect between the two, the effects of improving construction fluidity, reducing the amount of water added, high water reduction rate and no segregation are achieved, thereby improving the overall performance of the castable.

[0025] Preferably, the composite anti-penetration improver is prepared by mixing carbon-containing resin powder Carbores P produced by Germany's Rega Company and asphalt in a mass ratio of 3:2.

[0026] By adopting the above technical solution, the composite anti-penetration improver is prepared by mixing the carbon resin powder Carbores P produced by Germany's Ruijia Company and asphalt in a mass ratio of 3:2, which has the following effects: 1. Improving the thermal shock stability of the castable: The carbon resin powder Carbores P has a high residual carbon content (residual carbon ≥ 80%), belongs to amorphous carbon, and has the advantages of small particle size, high reactivity, and easy graphitization. These characteristics enable the carbon resin powder Carbores P to improve the thermal shock resistance of the castable and improve its stability in high temperature environments. 2. Improving the anti-slag erosion and anti-penetration properties of the castable: Asphalt plays an important role in the castable. After being heated and softened, it penetrates or volatilizes and condenses into the gaps or pores of the castable, which can enhance the bonding between particles, improve the liquid phase distribution at high temperature, avoid over-sintering, and significantly improve the anti-slag performance of the castable. At the same time, the carbon resin powder Carbores P and asphalt work synergistically to significantly improve the comprehensive performance of the castable. 3. Improve the high temperature creep and corrosion resistance of the castable: Carbores P, a carbon resin powder, has a high residual carbon content, which can improve the thermal shock resistance, high temperature creep, corrosion resistance and penetration resistance of the castable. This makes the castable have better durability and stability in high temperature environments. 4. Improve the internal pore refinement of the castable and enhance the bonding between particles: Asphalt has relatively good hydrophilicity, and will not cause a significant increase in water demand when used in castables, and has good dispersion properties. After heating (115-140℃) and softening, asphalt has good spreadability and high viscosity. It penetrates, volatilizes and condenses into the gaps or pores of the aggregate interface and the matrix, which can refine the internal pores of the castable and enhance the bonding between particles. In summary, the composite anti-penetration improver is prepared by mixing Carbores P, a carbon-containing resin powder produced by Germany's Rega Company, and asphalt in a mass ratio of 3:2. Its main function in this application is to improve the thermal shock stability, slag erosion resistance and anti-penetration performance, high-temperature creep and corrosion resistance of the castable, as well as to miniaturize the pores inside the castable and enhance the bonding effect between particles.

[0027] In a second aspect, the present application provides a method for preparing a castable material resistant to slag corrosion, which adopts the following technical solution:

[0028] The present application also provides a method for preparing the above-mentioned castable for resisting slag corrosion, comprising the following steps: according to the mass proportions, modified aluminum-chromium-zirconium corundum aggregate, modified corundum hollow balls, alumina fine powder, fused aluminum-magnesium spinel fine powder, modified chopped zirconium refractory fiber, coke fine powder, kyanite powder, alumina micropowder, spodumene powder, binder, water reducer and composite anti-penetration improver are mixed and stirred uniformly to obtain a castable for resisting slag corrosion.

[0029] In summary, the beneficial technical effects of this application are:

[0030] 1. Simple preparation, low cost, energy saving and environmental protection: The modified aluminum-chromium-zirconium-corundum aggregate is made by compounding and modifying fine particles of fused-cast zirconium-corundum waste bricks and fine particles of aluminum-chromium waste bricks, which makes full use of waste resources and reduces costs; at the same time, the preparation process avoids harm to the human body and pollution to the environment.

[0031] 2. High flexural strength and high compressive strength: The mechanical properties of the castable are improved by adding raw materials such as alumina fine powder and fused aluminum magnesium spinel fine powder.

[0032] 3. Excellent thermal insulation performance and thermal shock resistance: The addition of coke can further ensure the high-temperature strength of the castable; coke gemstone fine powder has excellent thermal shock stability and high-temperature performance, which improves the comprehensive performance of the castable.

[0033] 4. Anti-slag erosion and anti-penetration performance: The modified aluminum-chromium-zirconium corundum aggregate has extremely strong resistance to aluminum liquid erosion and penetration, which greatly improves the anti-slag erosion and anti-penetration performance of the castable; the composite anti-penetration improver is made by mixing carbon-containing resin powder Carbores P and asphalt, which significantly improves the anti-slag performance of the castable.

[0034] 5. The castable has a long shelf life and does not pollute the aluminum liquid: a dense oxide film is formed on the surface of the modified aluminum-chromium-zirconium corundum aggregate in a short time, thereby improving the corrosion resistance and anti-penetration performance of the aluminum-chromium-zirconium corundum aggregate; the carbon-containing resin powder Carbores P and asphalt work synergistically to significantly improve the comprehensive performance of the castable (thermal shock stability, slag erosion resistance and anti-penetration performance). DETAILED DESCRIPTION

[0035] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0036] In the following examples, preparation examples and comparative preparation examples, 1 part means 100 g.

[0037] Preparation Example 1 Preparation of modified aluminum-chromium-zirconium corundum aggregate

[0038] The preparation method of modified aluminum-chromium-zirconium corundum aggregate comprises the following steps:

[0039] S11. According to the mass proportions, 100 parts of fine particles of fused zirconium corundum waste bricks with a particle size of 0.1-0.2 mm and 500 parts of fine particles of aluminum chromium waste bricks with a particle size of 0.1-0.2 mm were mixed evenly to obtain a mixture A. The mixture A was then poured into a rolling ball mill, and a passivating agent was sprayed into the ball mill. The working parameters of the ball mill were adjusted to: a speed of 100 r / min, a power of 1500 kW, and a ball milling time of 2.5 hours to obtain a mixture B. The spraying frequency of the passivating agent was 1 time / min, and the spraying dosage was 5 mL / cm 2 ; The passivating agent is prepared by: according to the mass parts, 55 parts of sodium metasilicate, 15 parts of straw charcoal, 8 parts of dodecyltrimethylammonium chloride and 22 parts of deionized water are stirred and mixed uniformly to obtain a passivating agent;

[0040] S12. According to the mass proportion, 600 parts of mixed material B are used as raw materials to form a plate-shaped material layer with a thickness of 130 mm in a seat-cooled electric arc furnace. After arcing, 90 parts of coke material are sprinkled on the surface of the plate-shaped material layer at a frequency of 10 parts / min within 10 minutes, and the temperature in the furnace is adjusted to control 1600°C. After reacting for 9 hours, modified aluminum-chromium-zirconium corundum aggregate is prepared.

[0041] Preparation Example 2 Preparation of modified corundum hollow spheres

[0042] The preparation method of modified hollow corundum spheres is as follows: according to the mass fraction, 100 parts of hollow corundum spheres with a particle size of 1 mm are immersed in 200 parts of aluminum titanate solution with a mass concentration of 40% for 24 hours. The hollow corundum spheres after immersion are filtered and dried at 850°C to obtain modified hollow corundum spheres.

[0043] Preparation Example 3 Preparation of modified short-cut zirconium-containing refractory fibers

[0044] The modification method of modified short-cut zirconium-containing refractory fiber comprises the following steps:

[0045] S41, according to the mass fraction, adding 10 parts of nano-montmorillonite to 20 parts of hydrochloric acid solution with a mass concentration of 25%, treating at 120° C. for 1.5 h, collecting the precipitate by filtration, washing and drying to obtain modified montmorillonite;

[0046] S42. According to the mass proportions, 10 parts of modified montmorillonite, 40 parts of short-cut zirconium-containing refractory fibers with a length of 5-10 mm, 110 parts of magnesium chloride and 120 parts of aluminum chloride are added to 1500 parts of a 6% aqueous sodium hydroxide solution. After ultrasonic dispersion for 1 hour, the mixture is heated to 125°C under a nitrogen protective atmosphere for reaction for 22 hours. After drying, the modified short-cut zirconium-containing refractory fibers are obtained.

[0047] Preparation Comparative Example 1 Preparation of aluminum-chromium-zirconium corundum mixed aggregate

[0048] The preparation method of aluminum-chromium-zirconium corundum mixed aggregate comprises the following steps:

[0049] According to the mass fraction, 100 parts of fine particles of fused zirconium corundum waste bricks with a particle size of 0.1-0.2 mm and 500 parts of fine particles of aluminum chromium waste bricks with a particle size of 0.1-0.2 mm were mixed evenly to obtain a mixture A, and then the mixture A was poured into a rolling ball mill, and a passivating agent was sprayed into the ball mill. The working parameters of the ball mill were adjusted to: speed 100r / min, power 1500kw, and ball milling time 2.5 hours to obtain aluminum chromium-zirconium corundum mixed aggregate; wherein the spraying frequency of the passivating agent was 1 time / min, and the spraying dosage was 5mL / cm 2 The preparation method of the passivator is as follows: according to the mass proportions, 55 parts of sodium metasilicate, 15 parts of straw charcoal, 8 parts of dodecyltrimethylammonium chloride and 22 parts of deionized water are stirred and mixed uniformly to obtain the passivator. Example 1

[0050] A castable for resisting slag corrosion, comprising the following raw materials by weight: 35 parts of modified aluminum-chromium-zirconium corundum aggregate, 10 parts of modified corundum hollow spheres, 8 parts of alumina fine powder (average particle size of 325 mesh), 10 parts of fused aluminum-magnesium spinel fine powder, 3 parts of modified short-cut zirconium-containing refractory fibers, 8 parts of coke sapphire fine powder (average particle size of 0.5 mm), 3 parts of kyanite powder (average particle size of 180 mesh), 5 parts of alumina micropowder (average particle size of 5 μm), 2 parts of spodumene powder (average particle size of 180 mesh), and a binder. 3 parts, 0.2 parts of water reducer, 3 parts of composite anti-penetration improver, the average particle size of the fused aluminum magnesium spinel fine powder is 325 mesh, the mass content of magnesium oxide in the fused aluminum magnesium spinel fine powder is 80%, the binder is calcium aluminate cement, and the weight percentage of aluminum oxide in the calcium aluminate cement is 75%, the water reducer is prepared by mixing aliphatic high-efficiency water reducer and polycarboxylic acid high-performance water reducer in a mass ratio of 4:5, and the composite anti-penetration improver is prepared by mixing carbon-containing resin powder Carbores P produced by Germany's Rega Company and asphalt in a mass ratio of 3:2.

[0051] The preparation method of the above-mentioned castable for resisting slag erosion comprises the following steps: according to the mass proportions, modified aluminum-chromium-zirconium corundum aggregate, modified corundum hollow balls, alumina fine powder, fused aluminum-magnesium spinel fine powder, modified chopped zirconium refractory fiber, coke fine powder, kyanite powder, alumina micropowder, spodumene powder, binder, water reducer and composite anti-penetration improver are mixed and stirred evenly to obtain a castable for resisting slag erosion. Example 2

[0052] A castable for resisting slag corrosion, comprising the following raw materials by weight: 40 parts of modified aluminum-chromium-zirconium corundum aggregate, 12 parts of modified corundum hollow balls, 10 parts of alumina fine powder (average particle size of 325 mesh), 12 parts of fused aluminum-magnesium spinel fine powder, 5 parts of modified short-cut zirconium-containing refractory fiber, 10 parts of coke sapphire fine powder (average particle size of 0.5 mm), 5 parts of kyanite powder (average particle size of 180 mesh), 6 parts of alumina micropowder (average particle size of 5 μm), 3 parts of spodumene powder (average particle size of 180 mesh), and a combination of 4 parts of agent, 0.3 parts of water reducing agent, 4 parts of composite anti-penetration improver, the average particle size of the fused aluminum magnesium spinel fine powder is 325 meshes, the mass content of magnesium oxide in the fused aluminum magnesium spinel fine powder is 80%, the binder is calcium aluminate cement, and the weight percentage content of aluminum oxide in the calcium aluminate cement is 75%, the water reducing agent is prepared by mixing aliphatic high-efficiency water reducing agent and polycarboxylic acid high-performance water reducing agent in a mass ratio of 4:5, and the composite anti-penetration improver is prepared by mixing carbon-containing resin powder Carbores P produced by Germany's Rega Company and asphalt in a mass ratio of 3:2.

[0053] The preparation method of the above-mentioned castable for resisting slag erosion comprises the following steps: according to the mass proportions, modified aluminum-chromium-zirconium corundum aggregate, modified corundum hollow balls, alumina fine powder, fused aluminum-magnesium spinel fine powder, modified chopped zirconium refractory fiber, coke fine powder, kyanite powder, alumina micropowder, spodumene powder, binder, water reducer and composite anti-penetration improver are mixed and stirred evenly to obtain a castable for resisting slag erosion. Example 3

[0054] A castable for resisting slag corrosion, comprising the following raw materials by mass: 38 parts of modified aluminum-chromium-zirconium corundum aggregate, 11 parts of modified corundum hollow spheres, 9 parts of alumina fine powder (average particle size of 325 mesh), 11 parts of fused aluminum-magnesium spinel fine powder, 4 parts of modified short-cut zirconium-containing refractory fiber, 9 parts of coke sapphire fine powder (average particle size of 0.5 mm), 4 parts of kyanite powder (average particle size of 180 mesh), 5.5 parts of alumina micropowder (average particle size of 5 μm), 2.5 parts of spodumene powder (average particle size of 180 mesh), 3 parts of binder .5 parts, 0.25 parts of water reducer, 3.5 parts of composite anti-penetration improver, the average particle size of the fused aluminum magnesium spinel fine powder is 325 mesh, the mass content of magnesium oxide in the fused aluminum magnesium spinel fine powder is 80%, the binder is calcium aluminate cement, the weight percentage of aluminum oxide in the calcium aluminate cement is 75%, the water reducer is prepared by mixing aliphatic high-efficiency water reducer and polycarboxylic acid high-performance water reducer in a mass ratio of 4:5, and the composite anti-penetration improver is prepared by mixing carbon-containing resin powder Carbores P produced by Germany's Rega Company and asphalt in a mass ratio of 3:2.

[0055] The preparation method of the above-mentioned castable for resisting slag erosion comprises the following steps: according to the mass proportions, modified aluminum-chromium-zirconium corundum aggregate, modified corundum hollow balls, alumina fine powder, fused aluminum-magnesium spinel fine powder, modified chopped zirconium refractory fiber, coke fine powder, kyanite powder, alumina micropowder, spodumene powder, binder, water reducer and composite anti-penetration improver are mixed and stirred evenly to obtain a castable for resisting slag erosion.

[0056] Comparative Example 1

[0057] The same as Example 3, except that an equal amount of the aluminum-chromium-zirconium corundum mixed aggregate prepared in Preparation Comparative Example 1 is used instead of the modified aluminum-chromium-zirconium corundum aggregate.

[0058] Comparative Example 2

[0059] The same as Example 3, except that an equal amount of short-cut zirconium-containing refractory fibers with a length of 5-10 mm is used instead of the modified short-cut zirconium-containing refractory fibers.

[0060] Comparative Example 3

[0061] The same as Example 3, except that an equal amount of hollow corundum spheres with a particle size of 1 mm are used instead of the modified hollow corundum spheres.

[0062] Comparative Example 4

[0063] The same as Example 3, except that the water reducer is an aliphatic high-efficiency water reducer.

[0064] Comparative Example 5

[0065] The same as Example 3, except that the water reducer is a polycarboxylic acid-based high-performance water reducer.

[0066] Comparative Example 6

[0067] The same as Example 3, except that the composite anti-penetration improver is carbon-containing resin powder Carbores P produced by Germany's Rega Company.

[0068] Comparative Example 7

[0069] The same as Example 3, except that the composite anti-penetration improving agent is asphalt.

[0070] Performance Testing

[0071] 5% water of the total mass of the castable was added to the castables for resisting slag corrosion prepared in Examples 1 to 3 and Comparative Examples 1 to 7, respectively, the mixture was mixed and stirred, cast and molded, dried at 110°C for 24 hours, and kept warm at 1350°C for 3 hours to obtain refractory materials. The following tests were performed, and the test results are shown in Table 1.

[0072] Flexural strength: Refer to the method of GB / T 3001-2017 "Test method for flexural strength of refractory materials at room temperature" to test the flexural strength;

[0073] Compressive strength: refer to GB / T 5072-2008 "Test method for compressive strength of refractory materials at room temperature" to test the compressive strength;

[0074] Thermal conductivity: Refer to GB / T5990-2006 "Test method for thermal conductivity of refractory materials" to test the thermal conductivity.

[0075] Thermal shock resistance test method: The refractory material is subjected to 10 cycles of testing between two temperatures of 15°C and 145°C to detect the crack rate on the surface of the product;

[0076] Line change rate: Test sample line change rate in accordance with GB / T5988-2007;

[0077] Slag erosion resistance and permeability: According to GB / T8931-2007, the static crucible method is used to study the slag resistance of the castable: 20g of aluminum slag is placed in the prepared crucible sample and kept at 1600℃ for 3h. After cooling, the sample is cut along the center line, and the erosion area percentage and permeability area percentage are calculated to measure the slag erosion resistance and permeability of the castable.

[0078] Table 1 Performance test

[0079]

[0080] Analyzing the data in Table 1, we can see that:

[0081] 1) The castables for resisting slag erosion prepared in Examples 1 to 3 have high flexural strength and high compressive strength, as well as excellent thermal insulation performance, thermal shock stability, resistance to slag erosion and penetration, a long castable storage period, and no pollution to molten aluminum.

[0082] 2) The comparative analysis of the performance of the castables for resisting slag erosion prepared in Example 3 and Comparative Example 1 shows that the modified aluminum-chromium-zirconium corundum aggregate prepared in the present application has multiple effects and synergistic effects in the castable, such as resisting slag erosion, resisting penetration, resisting thermal shock stability, improving the strength of the castable and environmental protection performance.

[0083] 3) The comparative analysis of the performance of the castables for slag erosion resistance prepared in combination with Example 3 and Comparative Example 2 shows that the chopped zirconium-containing refractory fiber itself has good high temperature resistance. After the modification treatment, its dispersibility and wettability in the castable are improved, so as to better exert its high temperature resistance. This is of great significance for improving the service life and stability of the castable in a high temperature environment. The modified short chopped zirconium-containing refractory fiber and other raw materials (such as modified aluminum-chromium-zirconium corundum aggregate, alumina fine powder, etc.) work together to make the castable have excellent slag erosion resistance, thermal insulation, thermal shock stability and anti-penetration performance.

[0084] 4) The performance comparison analysis of the castable for slag erosion resistance prepared in combination with Example 3 and Comparative Example 3 shows that the role of the modified corundum hollow spheres is to improve the thermal insulation performance and thermal shock resistance stability of the castable. Since the hollow corundum spheres have a lower thermal conductivity and a higher strength, adding them to the castable can effectively reduce heat transfer, thereby improving the thermal insulation performance of the castable. At the same time, the addition of the hollow corundum spheres can also increase the internal porosity of the castable, so that it has better thermal shock resistance stability. The modified hollow corundum spheres can improve the overall performance of the castable, so that the castable has the advantages of good thermal insulation performance, thermal shock resistance stability, slag erosion resistance and anti-penetration performance while maintaining high mechanical properties.

[0085] 5) The comparative analysis of the performance of the castables for resisting slag erosion prepared in combination with Example 3 and Comparative Examples 4-5 shows that the water reducer is prepared by mixing an aliphatic high-efficiency water reducer and a polycarboxylic acid-based high-performance water reducer in a mass ratio of 4:5. Through the synergistic effect between the two, the effects of improving construction fluidity, reducing the amount of water added, and achieving a high water reduction rate without segregation are achieved, thereby improving the overall performance of the castable.

[0086] 6) The comparative analysis of the performance of the castables for resisting slag erosion prepared in combination with Example 3 and Comparative Examples 6-7 shows that the composite anti-permeation improver is prepared by mixing the carbon-containing resin powder Carbores P produced by Germany's Rega Company and asphalt in a mass ratio of 3:2. Through the synergistic effect between the two, the thermal shock stability, slag erosion resistance and anti-permeation performance, high-temperature creep and corrosion resistance of the castable are improved, the pores inside the castable are miniaturized, and the bonding effect between particles is enhanced.

[0087] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.

Claims

1. A castable for resisting slag erosion, characterized in that: The preparation raw materials include the following by weight: 35-40 parts of modified aluminum-chromium-zirconium corundum aggregate, 10-12 parts of modified corundum hollow spheres, 8-10 parts of alumina fine powder, 10-12 parts of fused aluminum-magnesium spinel fine powder, 3-5 parts of modified short-cut zirconium-containing refractory fibers, 8-10 parts of coke gemstone fine powder, 3-5 parts of kyanite powder, 5-6 parts of alumina micropowder, 2-3 parts of spodumene powder, 3-4 parts of binder, 0.2-0.3 parts of water reducer, and 3-4 parts of composite anti-penetration improver; The preparation method of the modified aluminum-chromium-zirconium corundum aggregate comprises the following steps: S11. According to the mass proportions, 100 parts of fine particles of fused zirconium corundum waste bricks with a particle size of 0.1-0.2 mm and 500 parts of fine particles of aluminum chromium waste bricks with a particle size of 0.1-0.2 mm are mixed evenly to obtain a mixture A, and then the mixture A is poured into a rolling ball mill, and a passivating agent is sprayed into the ball mill. The working parameters of the ball mill are adjusted to: a speed of 100 r / min, a power of 1500 kW, and a ball milling time of 2-3 hours to obtain a mixture B; wherein the spraying frequency of the passivating agent is 1 time / min, and the spraying dosage is 5 mL / cm 2 ; S12, according to the mass fraction, 600 parts of the mixed material B are used as raw materials to form a plate-shaped material layer with a thickness of 130 mm in a seat-cooled electric arc furnace, and after arcing, 80-100 parts of coke material are sprinkled on the surface of the plate-shaped material layer at a frequency of 10 parts / min within 10 minutes, and the temperature in the furnace is adjusted to control 1600°C. After reacting for 8-10 hours, a modified aluminum-chromium-zirconium corundum aggregate is prepared; The preparation method of the passivating agent is as follows: according to the mass proportions, 55 parts of sodium metasilicate, 15 parts of straw charcoal, 8 parts of dodecyltrimethylammonium chloride and 22 parts of deionized water are stirred and mixed uniformly to obtain the passivating agent; The preparation method of the modified hollow corundum spheres is as follows: according to the mass fraction, 100 parts of hollow corundum spheres with an average particle size of 1 mm are immersed in 200 parts of aluminum titanate solution with a mass concentration of 40% for 24 hours, the immersed hollow corundum spheres are filtered, and dried at a temperature of 850° C. to obtain the modified hollow corundum spheres; The modification method of the modified short-cut zirconium-containing refractory fiber comprises the following steps: S41, adding 10 parts of nano-montmorillonite to 20 parts of 25% hydrochloric acid solution by mass, treating at 120° C. for 1.5 h, collecting the precipitate by filtration, washing and drying to obtain modified montmorillonite; S42, adding modified montmorillonite, short-cut zirconium-containing refractory fibers with a length of 5-10 mm, magnesium chloride and aluminum chloride to a sodium hydroxide aqueous solution with a mass concentration of 6% according to the mass fractions, ultrasonically dispersing for 1 hour, heating to 125° C. under a nitrogen atmosphere for reaction for 20-24 hours, and drying to obtain modified short-cut zirconium-containing refractory fibers; The water reducer is prepared by mixing an aliphatic high-efficiency water reducer and a polycarboxylic acid-based high-performance water reducer in a mass ratio of 4:5; The composite anti-penetration improver is prepared by mixing carbon-containing resin powder Carbores P produced by Germany's Rega Company and asphalt in a mass ratio of 3:

2.

2. A castable for resisting slag corrosion according to claim 1, characterized in that: The mass ratio of the modified montmorillonite, the short-cut zirconium-containing refractory fiber with a length of 5-10 mm, magnesium chloride, aluminum chloride and the sodium hydroxide aqueous solution with a mass concentration of 6% is 1:4:11:12:

150.

3. A castable for resisting slag corrosion according to claim 1, characterized in that: The average particle size of the pyroxene fine powder is 0.5 mm, the average particle size of the kyanite powder is 180 mesh, the average particle size of the alumina micropowder is 5 μm, the average particle size of the spodumene powder is 180 mesh, the average particle size of the alumina fine powder is 325 mesh, the average particle size of the fused aluminum magnesium spinel fine powder is 325 mesh, and the mass content of magnesium oxide in the fused aluminum magnesium spinel fine powder is 80%.

4. A castable for resisting slag corrosion according to claim 1, characterized in that: The binder is calcium aluminate cement, and the weight percentage of aluminum oxide in the calcium aluminate cement is 75%.

5. A method for preparing a castable for resisting slag corrosion according to any one of claims 1 to 4, characterized in that: The following steps are involved: Modified aluminum-chromium-zirconium corundum aggregate, modified corundum hollow spheres, alumina fine powder, fused aluminum-magnesium spinel fine powder, modified chopped zirconium-containing refractory fiber, coke fine powder, kyanite powder, alumina powder, spodumene powder, binder, water reducer and composite anti-penetration improver are mixed and stirred in proportions by mass to obtain a castable for resisting slag erosion.

Citation Information

Patent Citations

  • Aluminum-containing hollow sphere light-weight brick and preparation method thereof

    CN102557698A

  • Refractory material granules with aluminum titanate coatings and preparation method thereof

    CN102584269A